Distribuição e partição geoquímica de metais traço na Costa Norte de Fortaleza, Ce - Maia, Saulo Robério Rodrigues (2004)
The coastal zone of Ceará State corresponds to only 14.38% of the State’s territory but harbors about 48.9% of its total population. The Metropolitan Region of Fortaleza (RMF), the State’s Capital population density at the coastal zone reaches 598 inhab/km2, and 6.814 inhab/km2 when only the city of Fortaleza itself is considered. During the 1970’s, Fortaleza witnessed an accelerated and unplanned urban growth along its coastal zone including engineering works, which affected the coastline itself, including the Fortaleza Harbor and may have increased pollutants emissions to the coastal region. Therefore, this study aims to evaluate the influence of these antropogenic developments on the emissions of trace metals and their distribution and geochemical partitioning in bottom sediments collected along the RMF coastal region. In two field campaigns, in the rain and dry season, the concentrations of Hg, Cu, Cd, Pb, Zn, Fe and Al, were measured in bottom sediments of the coastal zone. There was no significant difference between the two campaigns for all trace metals, except for Fe. Measured concentrations varied between 0.72 to 17.54 ng.g-1 for Hg; 0.32 to 4.64 μg.g-1 for Cu; 0.13 to 0.77 μg.g-1 for Cd; 3.29 to 13.00 μg.g-1 for Pb; 1.81 to 18.64 μg.g-1 for Zn; 0.78 to 9.12 mg.g-1 for Al, 0.76 to 9.27 mg.g-1 (rain season) and 1.28 to 13.92 mg.g-1 (dry season) for Fe. All trace metals concentrations presented significant positive correlation with the major geochemical carries analyzed, i.e. organic matter content, Aluminum and Iron, except for carbonates, carbonates are not efficient carriers of metals in these metals. Although the oceanic water mass acts as a large diluter of contaminants, areas of higher trace metal concentrations were observed close to the shoreline, at the area of influence of the Fortaleza Harbor and near the outlet of a submarine wastewater outfall. Concentrations decrease in an E-W direction following the littoral drift. The submarine wastewater outfall of Fortaleza showed an important point source of Hg, Cu, Zn, Cd and Pb. Although absolute concentrations of these trace metals were, in general, low. The higher concentrations along the shoreline suggest that urban runoff is also a significant source of trace metals, in particular of Cd and Pb. The spatial distribution of trace metals concentrations showed two important factors determining the behavior of trace metals in the bottom sediments of the RMF. The first factor is related to the concentrations of the geochemical carriers, which influence the behavior of Cu, Pb and Zn. The second factor is the proximity and/or the intensity of area sources and dominated the behavior of Hg and Cd.